Effect of Chlorella vulgaris extract on high sucrose diet-induced diabetes in Drosophila melanogaster - Mohamad Agus Salim; Muhammad Subandi; Yeni Yuniarti (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2021)
Microalgae Chlorella vulgaris is a microscopic green alga known to have potential as a source of food and medicine (functional food). However, the pharmacological capacity of these microalgae species against disease due to metabolic disorders is not understood. Therefore, this study aims to evaluate the effect of C. vulgaris extract on animal models of Drosophila melanogaster, which are fed with a high-sucrose diet (HSD). In this study, the wild-type Drosophila used for seven days of observation was divided into four groups. The first group was used as a control without treatment, the second was treated with HSD (30%), the third was treated with C. vulgaris extract (120 g/L), and the fourth group had double treatment (HSD and C. vulgaris extract). Meanwhile, the parameters observed included fecundity, hatchability, hemolymph glucose, and triglyceride levels. The results showed that the C. vulgaris extract was able to reduce the negative effects of administering HSD. In addition, the single and double treatment of C. vulgaris extract and HSD significantly decreased the levels of hemolymph glucose as well as triglycerides of Drosophila. At the same time, the fecundity parameters and hatchability significantly increased compared to Drosophila that received only HSD treatment. Based on these results, C. vulgaris extract the has potential to be used as an antihyperglycemic agent. However, further study is recommended to prove it.